Government bond rates and interest expenditure of large euro area member states: A scenario analysis - Veronika Grimm; Lukas Nöh; Volker Wieland (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2022)
This paper assesses the possible development of government interest expenditures as a share of GDP for Germany, France, Italy and Spain. Until 2021, these and other member states could anticipate a further reduction of interest expenditure in the future. This outlook has changed considerably with the recent surge in inflation and government bond rates. Nevertheless, under reasonable assumptions current yield curves still imply that interest expenditure relative to GDP can be stabilized at the current level. We also review the implications of a further upward shift in the yield curves of 1 or 2 percentage points. They suggest significant medium-term risks for highly indebted member states with interest expenditure approaching or exceeding levels last observed on the eve of the euro area debt crisis. In light of these risks, governments of euro area member states should take substantive action to achieve a sustained decline in debt-to-GDP ratios towards safer levels. They bear the responsibility for making sure that government finances can weather the higher interest rates which are required to achieve price stability in the euro area.
Keywords: 330